Promotion of improved sesame technologies in selected agricultural growth program-II districts of harari region - Ibsa Aliyi Usmane; Abdulaziz Teha Umer (Open Journal of Plant Science - Peertechz Publications, 2020)
Small holder farmers face the problem of dietary diversity and income generation in their living system. To alleviate this problem this research activity was conducted at Harari Region with objectives of demonstrate improved sesame varieties on farmers land develop the knowledge and skill of farmers and other stakeholders have on sesame food utilization and strengthen the institutional and other stakeholders linkages on agricultural research outputs. Two improved sesame variety Obsa and Dicho were evaluated and demonstrated on 10 farmers' fields on a plot sized 100 m2 along with the local check. In Kile kebele, two Farmers Research Groups comprising of 15 farmers were established to evaluate and select the better yielding variety. The yield performance of the improved varieties (Dicho, Obsa and local) were 3.85 qt/ha, 3.65 qt/ha and 2.73 qt/ha at Sofi district respectively. The yield obtained has statistically significant difference at 1% probability level between improved and local variety. Obsa and Dicho varieties were preferred by farmers for its high yielding, disease tolerant, seed colors and test. The result indicated that Dicho and Obsa varies have yield advantage (3.85 qt/ha) and (3.65qt/ha) when compared with local check. Therefore; both Obsa and Dicho varieties were recommended for further scale up/out in Harari Region to widen the horizon of the technology in the area and to reach more number of farmers.